ANALISIS PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Konsumen Produk Obat Coparcetin di Kota Semarang) - Rachma Ananti, Dian Laksmi; Tri Astuti, Sri Rahayu (Diponegoro Journal of Management, 2018)
This research is conducted with the background on the phenomenon of the amount number of complaints. Increased number of complaints will lead to dissatisfied customer and will affect to customer loyalty. The purpose of this research is to determine the influence of product quality in influencing customer satisfaction in order to increase customer loyalty of Coparcetin’s customer in Semarang.                  The population used in this study is all consumers who have made purchases of Coparcetin products. The collection of data obtained from 152 respondents, this study used 3 variables, 12 indicators, and 3 hypotheses. The analytical process used is quantitative method with AMOS analysis tool.             The results of this study indicate that product quality are giving positive and significant influence on customer satisfaction, product quality is also giving positive and significant to customer loyalty, and customer satisfaction are giving positive and significant influence on customer loyalty.